Objects of the Cripples' Training College (London & District) (circular) (1935)
1935 1935 1930s 1 page Cripples' Training College (LONDON & DISTRICT) LEATHERHEAD, SURREY. From Leatherhead Station (Southern Railway), 3 miles. From London, 20 miles. Hon. Treasurer: The Lord Moynihan, K.C.M.G., C.B. Secretary: Miss Grange Bankers: Westminister Bank Ltd. Objects (1) To enable those crippled persons, whose disability precludes them from being absorbed into industry in the normal way, to become fitted by suitable training. (2) To provide accommodation for a limited number of those whose disability renders them only capable of occupation under special institutional conditions but who can be employed on a partially economic basis in connection with the activities of the College. (3) In addition to the above, to provide facilities for those workers recently disabled who, whilst not requiring vocational training, need to achieve restoration of function and to learn to adapt themselves to the physical limitations imposed upon them by particular disablements. Type of trainee Over school age. At the outset, male sex only. It is intended to include a female section later. Admission On completion of Entrance Form to the satisfaction of the Selection Committee. The College is designed to serve primarily London and District but applications from other parts of the country will be considered, accommodation permitting. Fees 35/- per week at the outset. It is hoped to make a substantial reduction after the first year's running. Training given At the outset Training in the fundamental practice of simple electro-mechanical technique as carried out under industrial conditions, concurrently with the assembly and manufacture of articles related thereto on a commercial basis, with the gradual addition of other varieties of technical industrial training. Also, for a strictly limited number, training in typing and book-keeping, cooking and domestic work, general outdoor handyman and gardening work. Medical treatment Applicants in need of active treatment will not be eligible for admission. An orthopedic surgeon exercises general supervision and in the event of further hospital treatment becoming necessary, the trainee will be referred back to his original orthopaedic hospital or after care centre, if any. Otherwise, to an orthopaedic hospital with which special arrangements have been made. All communications should be sent to the London Office addressed to :— The Secretary, Cripples' Training College, 27, Marsham Street, Westminster, S.W.1. Telephone: Victoria 0654 from whom Entrance Forms and any further particulars can be obtained. J.B.S. & S. 3/35-A. 292/841.51/2/84